Genome sequence and description of Gracilibacillus timonensis sp. nov. strain Marseille‐P2481T, a moderate halophilic bacterium isolated from the human gut microflora. Issue 2 (19th April 2018) - Diop, Awa; Seck, El hadji; Dubourg, Gregory; Armstrong, Nicholas; Blanc‐Tailleur, Caroline; Raoult, Didier; Fournier, Pierre‐Edouard
Abstract: Microbial culturomics represents an ongoing revolution in the characterization of the human gut microbiota. By using three culture media containing high salt concentrations (10, 15, and 20% [w/v] NaCl), we attempted an exhaustive exploration of the halophilic microbial diversity of the human gut and isolated strain Marseille‐P2481 (= CSUR P2481 = DSM 103076), a new moderately halophilic bacterium. This bacterium is a Gram‐positive, strictly aerobic, spore‐forming rod that is motile by use of a flagellum and exhibits catalase, but not oxidase activity. Strain Marseille‐P2481 was cultivated in media containing up to 20% (w/v) NaCl, with optimal growth being obtained at 37°C, pH 7.0–8.0, and 7.5% [w/v] NaCl). The major fatty acids were 12‐methyl‐tetradecanoic acid and hexadecanoic acid. Its draft genome is 4, 548, 390 bp long, composed of 11 scaffolds, with a G+C content of 39.8%. It contains 4, 335 predicted genes (4, 266 protein coding including 89 pseudogenes and 69 RNA genes). Strain Marseille‐P2481 showed 96.57% 16S rRNA sequence similarity with Gracilibacillus alcaliphilus strain SG103 T, the phylogenetically closest species with standing in nomenclature. On the basis of its specific features, strain Marseille‐P2481 T was classified as type strain of a new species within the genus Gracilibacillus for which the name Gracilibacillus timonensis sp. nov. is formally proposed. Abstract : By using culture media containing high salt concentrations, we isolated a new Gracilibacillus strain from the human gut microbiota. Strain Marseille‐P248T exhibited a genome of 4, 548, 390 bp with a G+C content of 39.8%. It exhibited specific phenotypic and genetic features when compared with G. alcaliphilus and was classified as type strain of the new species G. timonensis sp. nov.